COMPARISON OF LOCOMOTOR AND MANIPULATIVE MOVEMENT ABILITY BASED ON HEIGHT IN ELEMENTARY SCHOOL CHILDREN - Ridho Pamungkas; Prayogi Dwina Angga; Usman Wahyudi (PROGRES PENDIDIKAN, 2022)
Locomotor and manipulative movements are basic movements that are important to be mastered at the age of 9-10 years because they can affect movement and play activities. The purpose of this study was to identify and compare the basic movements of children aged 9-10 years in the lowlands and highlands. This research is a comparative research with quantitative descriptive research with survey method. The results of the data that have been analyzed using the normality test in the lowlands obtained a significant value of 0.064 > 0.05, then the data is normally distributed. The results of the analysis of the normality test in the highlands have a significant value of 0.061 > 0.05, which means the data is normally distributed. The results of the homogeneity test got a significant value of 0.890 > 0.05, so the data was homogeneous. Then continued with the difference test, obtained a significant value of 0.004 < 0.05, which means that there is a significant difference. Based on the results of the analysis, it can be concluded that there are differences in locomotor and manipulative movements in the lowlands, which are lower than in the highlands.